Guide on wage order and minimum wage - Villanueva, Elvin B. (Quezon City, Philippines : Central Book Supply, 2010)
Wage Order is probably one of the most controversial issuance that the management deals with, particularly if it involves organized companies.
Chapter 1. What is wage order? -- Chapter 2. The minimum wage -- Chapter 3. Coverage of the wage order -- Chapter 4. Other wage exemptions requiring approval of application -- Chapter 5. How to seek exemption from wage order -- Chapter 6. Correcting wage distortion -- Chapter 7. Ruling if no employees receive salaries below minimum wage -- Chapter 8. Across the board wage increases -- Chapter 9. Wage increase and the collective bargaining agreements -- Chapter 10. the National wages and productivity commission -- Chapter 11. The regional tripartite wages and productivity board -- Chapter 12. Minimum wage determination.
With discussion on, Wage Order no. NCR-15/Php22.00 additional wage increase for NCR.
Keywords: MINIMUM WAGE -- LAW AND LEGISLATION -- PHILIPPINES